PENINGKATAN KEMAMPUAN BERPIKIR KREATIF MATEMATIS DAN KEMANDIRIAN BELAJAR SISWA SMP AR-RAHMAN MEDAN MELALUI PEMBELAJARAN OPEN-ENDED BERBASIS BRAIN-GYM - Siti Salamah Br. Ginting (AXIOM : Jurnal Pendidikan dan Matematika, 2019)
The purposes of the research were to determine: (1) the difference of improvement of students’ mathematical creative thingking ability (2) the difference of improvement of students’ self regulated learning, taught by open-ended based brain-gym and expository learning, (3) the interaction between learning method and students’ gender toward mathematics in increasing student’s mathematical creative thingking ability, and (4) the process of students’ answer in each learning. This research was quasi experimental research. The population of the research was all of the students at 7thgrade of Ar-Rahman Junior High School. The sample taken randomly, such as 7th-A (experiment class) and 7th-B (control class). The instruments of research were: (1) mathematical creative thinking ability test, and (2) self regulated learning scale. The result of trials to test mathematical creative thinking test are derived validity row by 0,640; 0,698; 0,709; 0,721; and 0,605 with a reliability test by 0,692. Data analysis was done using ANACOVA and ANAVA two ways formula. The results showed that (1) the improvement of mathematical creative thinking ability and self regulated learning students who received open-ended based brain-gym higher than students who received expository learning. (2) therewas no interaction between learning method and students’ gender toward mathematics in improvement student’s mathematical creative thingking ability, this is shown with significance value of 0.499 was greater than the significance level  = 0.05. (3) the process of answers of students who received open-ended learning-based brain-gym better than students who received expository. From this research, the researchers suggest to make good planning, attention to the characteristics of the students, efficient use of time, and for further research to be better explore further the others  capabilities.